Spanish-English Writing Structure Interferences in Second Language Learners - López Urdaneta, Julio Lorenzo (GIST – Education and Learning Research Journal, 2011)
Previous studies have drawn some results concerning the way in which second language (L2) students use their first language (L1) when producing texts in their L2. Therefore, this study examines the influence L1 written structure has on L2 written structure when students are asked to carry out assignments in the L2. To answer this question, twenty four students of the first semester at UNICA University were asked to write some papers in English during the semester. The results of this study indicated that the influence of L1 (Spanish) can definitely hinder the writing processes in L2. In addition, four basic mistakes in student papers were found to be a direct influence from L1 to L2 writing: word order, missing the verb “be”, implicit subject, and the incorrect use of the article “the.” Those mistakes emerged mostly due to the influence of their native language and also the lack of knowledge about the second language.